A novel Sporothrix brasiliensis genomic variant in Midwestern Brazil: evidence for an older and wider sporotrichosis epidemic (2020)
ABSTRACT: Sporotrichosis is a subcutaneous infection caused by fungi from the genus Sporothrix. It is transmitted by inoculation of infective particles found in plant-contaminated material or diseased animals, characterizing the classic sapronotic and emerging zoonotic transmission, respectively. Since 1998, southeastern Brazil has experienced a zoonotic sporotrichosis epidemic caused by S. brasiliensis, centred in the state of Rio de Janeiro. Our observation of feline sporotrichosis cases in Brasília (Midwestern Brazil), around 900 km away from Rio de Janeiro, led us to question whether the epidemic caused by S. brasiliensis has spread from the epicentre in Rio de Janeiro, emerged independently in the two locations, or if the disease has been present and unrecognized in Midwestern Brazil. A retrospective analysis of 91 human and 4 animal cases from Brasília, ranging from 1993 to 2018, suggests the occurrence of both sapronotic and zoonotic transmission. Molecular typing of the calmodulin locus identified S. schenckii as the agent in two animals and all seven human patients from which we were able to recover clinical isolates. In two other animals, the disease was caused by S. brasiliensis. Whole-genome sequence typing of seven Sporothrix spp. strains from Brasília and Rio de Janeiro suggests that S. brasiliensis isolates from Brasília are genetically distinct from those obtained at the epicentre of the outbreak in Rio de Janeiro, both in phylogenomic and population genomic analyses. The two S. brasiliensis populations seem to have separated between 2.2 and 3.1 million years ago, indicating independent outbreaks or that the zoonotic S. brasiliensis outbreak might have started earlier and be more widespread in South America than previously recognized.